Antimicrobial stewardship: from theory to reality in a resource-limited setting (and beyond) - Ochoa-Hein, Eric; Galindo-Fraga, Arturo (Frontiers in Antibiotics, 2024)
Correct use of antibiotics is paramount to present global health. Among other actions, antimicrobial stewardship emphasizes de-escalation and suspension whenever possible. Nonetheless, roadblocks can be encountered (e.g., lack of culture results or availability of specific antibiotic classes). Furthermore, in an ever-increasing interconnected world, global success relies on local success. In this perspective, a particular case study in a resource-limited setting is an example of the many difficulties encountered in the fight against antimicrobial resistance that could hamper global advancements.